Hubungan Pekerjaan, Nilai-Nilai Budaya, Penolong Persalinan dan Dukungan Keluarga dengan Pemberian ASI Eksklusif di Puskesmas Tena Teke - Stevani Florida Arin; Engelina Nabuasa; Amelya B. Sir (Universitas Nusa Cendana, 2021)
Exclusive breast milk is breast milk given to infants up to six months of age without giving any food or additional fluids. Tena Teke Primary Health Care (PHC) has low coverage of exclusive breastmilk as only 45% babies receiving the breastmilk; this percentage is under the national target of 80%. The research aimed to analyze the relationship between work, cultural values, childbirth assistance and family support with exclusive breastfeeding at Tena Teke PHC. This research was a quantitative study with a cross-sectional design. The sample consisted of 75 people selected using a simple random sampling technique. Data were analyzed using the chi square test with the significance level of α=0.05. The study found that the variable of maternal occupation (p=0.013), maternal cultural values (p=0.000), maternal birth attendant (p=0.003) and maternal family support (p=0.000) were associated with exclusive breastfeeding. Mothers who still actively work need to manage time to breastfeed their babies. Mothers are also encouraged to access information related to the benefits of exclusive breastfeeding to change the existing cultural perceptions about the traditions hindering exclusive breastfeeding practice.